2013
DOI: 10.1007/s11606-013-2349-9
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and Distress Among Internal Medicine Program Directors: Results of A National Survey

Abstract: BACKGROUND: Physician burnout and distress has been described in national studies of practicing physicians, internal medicine (IM) residents, IM clerkship directors, and medical school deans. However, no comparable national data exist for IM residency program directors. OBJECTIVE: To assess burnout and distress among IM residency program directors, and to evaluate relationships of distress with personal and program characteristics and perceptions regarding implementation and consequences of Accreditation Counc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 33 publications
(44 reference statements)
1
49
0
7
Order By: Relevance
“…Others have reported a lack of association between gender and burnout. 3,4,39 Dyrbye et al 4 also found in their study of physicians from all specialties that men were more satisfied than women with work-life balance. With the large percentage of women in pediatrics, an increased emphasis on improving work-life balance and career satisfaction among them is important.…”
Section: Discussionmentioning
confidence: 93%
“…Others have reported a lack of association between gender and burnout. 3,4,39 Dyrbye et al 4 also found in their study of physicians from all specialties that men were more satisfied than women with work-life balance. With the large percentage of women in pediatrics, an increased emphasis on improving work-life balance and career satisfaction among them is important.…”
Section: Discussionmentioning
confidence: 93%
“…The challenges described above all contribute to physician burnout, another factor that negatively impacts physician retention. Female physicians in particular demonstrate higher levels and manifestations of burnout . Female residents face gender‐specific challenges in addition to the stress typically associated with residency.…”
mentioning
confidence: 99%
“…2000;Dupras et al, 2012), explored difference between UBP and CBP programs and found a significantly higher prevalence of behavioral problems in resident in CBPs. Prevalence of higher burn out severity and prevalence of depersonalization and problems residents was significantly higher in internal medicine CBPS (West, 2013;Elmariah et al, 2017). Both studies were published after 2011 ACGME recommendations.…”
Section: Discussionmentioning
confidence: 95%
“…Six studies (Berkenblit, 2012;Khandelwal, 2018;Young, 2016;Jain, 2009, West, 2013 reported barriers to the adaptation of ACGME recommendations by residency programs (Table 6). We categorized barriers into factors that were related to faculty and resident, work support (Berkenblit, 2012, Khandelwal, 2018Young, 2016).…”
Section: Barriers For Scholarly Teaching and Learningmentioning
confidence: 99%